1997
DOI: 10.1164/ajrccm.155.6.9196088
|View full text |Cite
|
Sign up to set email alerts
|

Rhinovirus infection preferentially increases lower airway responsiveness in allergic subjects.

Abstract: Rhinovirus (RV) infections are important triggers of acute asthma symptoms in susceptible persons. To determine whether the presence of allergy is a risk factor for enhanced lower airway effects during RV infection, we experimentally infected (RV16) 18 volunteers with allergic rhinitis and 13 normal control subjects and measured the effects on the response of the lower airways to histamine. All subjects were successfully infected, as indicated by increased upper respiratory symptoms and RV16 cultured from nasa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
94
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(99 citation statements)
references
References 0 publications
4
94
1
Order By: Relevance
“…Only 2 days after HRV serotype 16 inoculation, the authors demonstrated increased airway hyperresponsiveness that augmented at days 7 and 15, and correlated with worsening of the asthma symptom score [129]. Experimental inoculation of HRV serotype 16 in volunteers with respiratory allergy also increases airway hyperresponsiveness to inhaled histamine [130] and, similar to the observation for methacholine, the change in histamine response caused by rhinovirus infection seems to be more significant in allergic subjects compared with non-allergic control subjects [131]. These data further support the concept that the presence of atopy may contribute to increased lower airway effects of rhinovirus infection.…”
Section: Rhinovirus Infection and Asthma Inductionmentioning
confidence: 64%
“…Only 2 days after HRV serotype 16 inoculation, the authors demonstrated increased airway hyperresponsiveness that augmented at days 7 and 15, and correlated with worsening of the asthma symptom score [129]. Experimental inoculation of HRV serotype 16 in volunteers with respiratory allergy also increases airway hyperresponsiveness to inhaled histamine [130] and, similar to the observation for methacholine, the change in histamine response caused by rhinovirus infection seems to be more significant in allergic subjects compared with non-allergic control subjects [131]. These data further support the concept that the presence of atopy may contribute to increased lower airway effects of rhinovirus infection.…”
Section: Rhinovirus Infection and Asthma Inductionmentioning
confidence: 64%
“…A synergistic relationship is evident between viral infection and allergen sensitization and exposure in provoking exacerbations, and the major trigger for exacerbations in both children and adults is viral infection (27)(28)(29). Clinical studies suggest that patients with asthma are more susceptible to rhinovirus infections than normal individuals, and sustain a longer duration of lower respiratory tract symptoms when infected with rhinoviruses (30)(31)(32). TSLP appears to be involved in the development of bronchial asthma through functional genetic polymorphisms that may contribute to Th2-polarized immunity through higher TSLP production by bronchial epithelial cells in response to viral respiratory infections.…”
Section: Discussionmentioning
confidence: 99%
“…In adults, they have been shown to increase airway responsiveness, even in subjects without clinical asthma (5), especially in allergic subjects (6); in mice, viral infections can enhance airway sensitization to allergen (7). Some, but not all studies have shown an association with acute asthma exacerbations (8)(9)(10)(11), especially when newer, sensitive virological detection methods are used (8).…”
mentioning
confidence: 99%